ALCOHOL-BASED ANTISEPTIC SOLUTIONS ARE INEFFECTIVE IN INHIBITING PATHOGENIC FUNGI - Handi Suyono; Laura Wihanto (JURNAL WIDYA MEDIKA, 2021)
Introduction: Breaking the chain of transmission of infection using an antiseptic solution is an easy, inexpensive and effective method. The incidence of fungal infection is one of the global health problems that lead to severe complications even death, especially in patients with immunosuppressed or immunocompromised conditions and is reported to be increasing. Although alcohol-based antiseptic solutions are frequently used to prevent transmission of pathogenic organisms, these methods are rarely evaluated. Aim: Determine the susceptibility of three pathogenic fungi against alcohol-based antiseptic solutions with and without hydrogen peroxide addition. Methods: To determine the inhibition of the antiseptic solution against fungi, the Kirby & Bauer test disc diffusion method was used. After the petri dishes were incubated at 37° C for 24 hours, the diameter of the inhibition zones were measured using a caliper. The phenol coefficient test was carried out to compare the efficacy of an antimicrobial agent in this case alcohol-based antiseptic solutions against phenol. The phenol coefficient was applied as a test against Salmonella typhi, with a minimum score of 1, using the method according to SNI 1842: 2019. Result: The inhibition zone on Candida albicans ATCC 102231, Aspergillus niger, and Cryptococcus neoformans ATCC 14116 for solution A contains ethanol 80% v / v, glycerin 8% v / v, sterile water add 100% and solution B contains ethanol 80% v / v, H2O2 0.15% v / v, glycerin 8% v / v, add 100 sterile water % all were less than 6 mm which were classified as resistant. The result of the phenol coefficient test for solution A and B were 0.3 and 0.4 , which less than 1, indicated the antiseptic solutions were less effective than phenol. Conclusion: Antiseptic ethanol solution and a combination of ethanol + H2O2 were ineffective inhibits of pathogenic fungal growth. Further studies are needed to form a more potent antiseptic solution in order to improve management of fungal infections prevention.